Pelatihan Pemanfaatan Limbah Sayur Dan Buah Sebagai Eco-Enzyme Untuk Kesehatan Tubuh Dan Lingkungan Di RT 009/ RW 005 Kelurahan Srengseng Jakarta Barat - Eko Fibryanto; Rahmi v; Rosita Stefani; Marie Louisa; Caroline Septiani; inantya Putri Parahita; Felicia (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2023)
Garbage is the result of human daily activities that are no longer used. If processed with good procedures, organic waste can still be used as a useful product. Eco-enzyme is a versatile liquid produced from the fermentation process of organic matter, sugar and water which functions for mopping, washing clothes, plant growth factors and pest repellents. This community service activity is in the form of educating and training on the use of vegetable and fruit waste as an eco-enzyme for the community, namely the Ibu-Ibu Arisan of Srengseng Urban Village RT 009 RW 005 which is carried out directly. The results of this activity show an increase in the results of the pre-test to post-test scores with significant differences. This activity was carried out with a good level of success and enthusiasm because there were variations in the delivery of material through presentations, videos, questions and answers, to mentoring activities of making eco-enzymes together.